In Honor of Dr. Joseph Plumb Cochran, the Founder of the First Modern Iranian Medical School - Siamak Sheikhi; Kazhal Mobaraki; Jamal Ahmadzadeh; Ghazal Akhavan; Leila Derafshpour (Journal of Research on History of Medicine, 2020)
Urmia is located in the northwestern part of Iran with close proximity to Turkey and Iraq borders. Urmia has an important status in Iran’s medical history because it is the home of Iranian’s first modern medical school, established by Dr. Joseph Plumb Cochran in 1878. Joseph Plumb Cochran was born in an American missionary family in Urmia city. After graduating from New York University, School of Medicine, he returned to his birthplace in 1879 to establish the first teaching hospital in Iran which was called Westminster hospital. Even though he was very proficient in all the local languages of the region (Persian, Azari, Kurdish & Asori), he taught most of the courses in English and the first group of students graduated in 1883 under his direct supervision. The Medical School was well known for its top academic work in Iran. He worked for 27 years, visiting thousands of patients. Throughout these years, 28 physicians were graduated from this medical school. Dr. Joseph Plumb Cochran died at the age of 50 from Typhoid Fever and was buried in a small Christian cemetery in the village of Sir near the city of Urmia.